2008
DOI: 10.1002/jts.20307
|View full text |Cite
|
Sign up to set email alerts
|

The association of exposure, risk, and resiliency factors with PTSD among Jews and Arabs exposed to repeated acts of terrorism in Israel

Abstract: Israel has faced ongoing terrorism since the beginning of the Al

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
156
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 213 publications
(182 citation statements)
references
References 36 publications
23
156
0
3
Order By: Relevance
“…Th e results of the Ron's studies (2014;2016) substantiate these fi gures, with higher levels of PTSD symptoms reported among non-Jewish participants (Arab Muslims, Arab Christians, and Druze) than among the Jewish participants, as well as a signifi cantly higher rate of possible PTSD diagnosis among the non-Jewish participants compared to the rates among the Jewish participants. Th ese fi ndings are also in line with those of other studies conducted in Israel, which have found that individuals of the Israeli-Palestinians Arab minority experience psychological symptoms and symptoms of depression at higher levels than do their Jewish counterparts, and that they exhibit a higher incidence of possible PTSD diagnosis following traumatic events, compared to the rates found among the Jewish participants (Hobfoll et al 2008;Yahav, Cohen 2007). Similar to Ron's studies (2014;2016), Yahav and Cohen found higher levels of Acute Stress Disorder (ASD) among the Arab population aft er the Second Lebanon War.…”
Section: Ethnicity Diff Erencessupporting
confidence: 90%
“…Th e results of the Ron's studies (2014;2016) substantiate these fi gures, with higher levels of PTSD symptoms reported among non-Jewish participants (Arab Muslims, Arab Christians, and Druze) than among the Jewish participants, as well as a signifi cantly higher rate of possible PTSD diagnosis among the non-Jewish participants compared to the rates among the Jewish participants. Th ese fi ndings are also in line with those of other studies conducted in Israel, which have found that individuals of the Israeli-Palestinians Arab minority experience psychological symptoms and symptoms of depression at higher levels than do their Jewish counterparts, and that they exhibit a higher incidence of possible PTSD diagnosis following traumatic events, compared to the rates found among the Jewish participants (Hobfoll et al 2008;Yahav, Cohen 2007). Similar to Ron's studies (2014;2016), Yahav and Cohen found higher levels of Acute Stress Disorder (ASD) among the Arab population aft er the Second Lebanon War.…”
Section: Ethnicity Diff Erencessupporting
confidence: 90%
“…Factors affecting larger groups of people have also been explored, such as social crises and disasters, as, for example, growing up in areas with high rates of poverty and violence (Luthar 1999), or surviving terrorist attacks (Hobfoll et al 2008). Even natural disasters such as hurricanes (Werner and Smith 1992) Werner and Smith (1992).…”
Section: Risks As Sources Of Mental Stress and Traumamentioning
confidence: 99%
“…Surveys have shown that more than two thirds of Americans felt depressed after the attacks on 11 September 2001 and more than one third indicated that they tried to avoid exposure to terrorism by changing their everyday behaviour around others because they were concerned that they or their family members could become victims of terrorism (Huddy et al, 2002: 422f.). These effects were even found for those not directly affected by terrorism; they identified with the victims and experienced increased distress (Hobfoll et al, 2008). We also see evidence of this increased concern in the media coverage of such incidents: terrorist attacks in Western countries are covered more extensively than deadlier attacks outside the Western world (see also Fischhoff et al, 2003).…”
Section: Threat Perceptionmentioning
confidence: 66%